Glencoe literature : the reader's choice ; course 5 - Ann Chin, Beverly; Wolfe, Denny; Copeland, Jeffrey S. (New York : Glencoe / McGraw-Hill, 2002)
Language and Literature
Keywords: Literature; Reader choice